I Sense A Disturbance in the Force: Mobile Device Interaction with Force Sensing - Scott, James; Brown, Lorna M.; Molloy, Mike (Microsoft Research, 2008)
We propose a new type of input for mobile devices by sensing forces such as twisting and bending applied by users. Deformation of the devices is not necessary for such “force gestures” to be detectable. Our prototype implementation augments an ultra-mobile PC (UMPC) to detect twisting and bending forces. We detail example interactions using these forces, employing twisting to perform application switching (alt-tab) and interpreting bending as page-down/up. By providing visual feedback related to the force type applied, e.g. of an application window twisting in 3D to reveal another and of pages bending across, these force-based interactions are made easy to learn and use. We also present a user study exploring users’ abilities to apply forces to various degrees, and draw implications from this study for future force-based interfaces.